Peramalan Titik Akuifer Di Desa Manistutu Kecamatan Melaya Kabupaten Jembrana Dengan Metode Geolistrik - Sukarasa, Ketut; Suardana, Putu (Universitas Hamzanwadi, 2023)
Research has been carried out which aims to determine the depth of the aquifer point in Manistutu Village, Melaya District, Jembrana Regency. The work process of this research is the first to collect data directly using a geoelectric device with a Wenner configuration. Electric current is passed below the earth's surface through current electrodes that are installed above the earth's surface. The data that has been collected is then processed using Res2Div version 3.53g for 2D. The result of the software is a 2D image which is a direct lateral view of the subsurface structure. Of the two identified paths, namely line 1 at initial coordinates 8°31'92.33